Civilization Identity of Russia as Vector of a Modern State Policy - Shamil Abdulaevich Alybegilov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article formation of political civilization identity of Russia is discussed. Authors open a problem of political unity of the Russian Federation through a prism of a problem of political identity